2017
DOI: 10.15252/embr.201642800
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐independent functions of DGCR8 are essential for neocortical development and TBR1 expression

Abstract: Recent evidence indicates that the miRNA biogenesis factors DROSHA, DGCR8, and DICER exert non-overlapping functions, and have also roles in miRNA-independent regulatory mechanisms. However, it is currently unknown whether miRNA-independent functions of DGCR8 play any role in the maintenance of neuronal progenitors and during corticogenesis. Here, by phenotypic comparison of cortices from conditional and knockout mice, we show that deletion, in contrast to depletion, leads to premature differentiation of neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 80 publications
6
53
2
Order By: Relevance
“…Indeed, a genome wide study of the human genome only found DGCR8 mRNAs to be downregulated by Drosha cleavage (Shenoy and Blelloch, 2009). However, there are at least two additional examples of mRNAs regulated by pri-miRNA stem-loops located in cis in mice: the transcription factors neurogenin 2 and T-box brain 1 (Chong et al, 2010; Knuckles et al, 2012; Marinaro et al, 2017). Interestingly, in most of these cases, the resulting miRNA is not thought to be expressed at a high enough level to be functional, unlike the KHSV and EBV miRNAs (Han et al, 2009; Knuckles et al, 2012; Marinaro et al, 2017; Sundaram et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a genome wide study of the human genome only found DGCR8 mRNAs to be downregulated by Drosha cleavage (Shenoy and Blelloch, 2009). However, there are at least two additional examples of mRNAs regulated by pri-miRNA stem-loops located in cis in mice: the transcription factors neurogenin 2 and T-box brain 1 (Chong et al, 2010; Knuckles et al, 2012; Marinaro et al, 2017). Interestingly, in most of these cases, the resulting miRNA is not thought to be expressed at a high enough level to be functional, unlike the KHSV and EBV miRNAs (Han et al, 2009; Knuckles et al, 2012; Marinaro et al, 2017; Sundaram et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that the ablation of DGCR8 impairs corticogenesis in mice more pronouncedly than Dicer depletion, a phenomenon caused by dysregulation of the T‐box brain protein 1 ( Tbr1 ) transcript, which has predicted hairpin structures in its coding sequence. However, the authors did not observe a change in Ngn2 levels and proposed the existence of distinct Microprocessor complexes with different target affinities . Drosha and DGCR8 are therefore important for maintaining the self‐renewal property of murine neural progenitors, which is achieved by destabilisation of transcripts that encode differentiation factors.…”
Section: Drosha and Dgcr8 In Mrna Destabilisationmentioning
confidence: 97%
“…The observation that the neural phenotypes of different knockout models for miRNA biogenesis factors (e.g. Dicer1, Drosha, Dgcr8) are distinct is in agreement with additional, noncanonical functions of these factors (Babiarz et al, 2011;Burger and Gullerova, 2015;Marinaro et al, 2017). Finally, even if one assumes that the loss of specific miRNAs underlies a phenotype in the Dicer1 KO brain, teasing apart the contribution of individual miRNAs is extremely challenging.…”
Section: Box 1 Insights From Dicer Conditional Knockoutsmentioning
confidence: 99%